Alcohol culture-2: culture of drink and drink in literature - Öncü, Fatih; Ögel, Kültegin; Çakmak, Duran (Journal of Dependence, 2002)
The alcohol subculture has began by the foundation of humanity. The usage of alcohol in different times and different communities formed lots of public and local sub-cultures. The origin of alcohol use tradition has been extanding to ancient times. Though the surroundings accompanying alcohol use has been changed, traditional factors influence use of alcohol to become widespread in the community. Alcohol use, just like any other issue in human life, has been a subject of interest in literature and it has mentioned sometimes praiseworthy and sometimes badly. No doubt; novels, poems and stories have got positive or negative effect on subcultural propagation and dissemination of alcohol. In this article, we reviewed many related articles and tried to describe the effect of alcohol in formation of subcultural groups and their social, literatural relationship!